1993
DOI: 10.1128/aem.59.8.2397-2403.1993
|View full text |Cite
|
Sign up to set email alerts
|

Dominating Role of an Unusual Magnetotactic Bacterium in the Microaerobic Zone of a Freshwater Sediment

Abstract: A combination of polymerase chain reaction-assisted rRNA sequence retrieval and fluorescent oligonucleotide probing was used to identify in situ a hitherto unculturable, big, magnetotactic, rod-shaped organism in freshwater sediment samples collected from Lake Chiemsee. Tentatively named "Magnetobacterium bavaricum," this bacterium is evolutionarily distant from all other phylogenetically characterized magnetotactic bacteria and contains unusually high numbers of magnetosomes (up to 1,000 magnetosomes per cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
174
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(188 citation statements)
references
References 42 publications
12
174
0
2
Order By: Relevance
“…Since cultivation attempts failed so far, we applied culture-independent characterization techniques, such as microsensor measurements, metagenomic analysis and MTB mass collection to further characterize 'Candidatus M. bavaricum'. In addition, refined structural analyses of magnetosome organization and sulfur globule content verified the previously hypothesized arrangement of magnetosome chains adjacent to the cell envelope and provides further evidence for a sulfur oxidizing metabolism of 'Candidatus M. bavaricum' (Spring et al, 1993;Hanzlik et al, 1996).…”
Section: Introductionsupporting
confidence: 73%
“…Since cultivation attempts failed so far, we applied culture-independent characterization techniques, such as microsensor measurements, metagenomic analysis and MTB mass collection to further characterize 'Candidatus M. bavaricum'. In addition, refined structural analyses of magnetosome organization and sulfur globule content verified the previously hypothesized arrangement of magnetosome chains adjacent to the cell envelope and provides further evidence for a sulfur oxidizing metabolism of 'Candidatus M. bavaricum' (Spring et al, 1993;Hanzlik et al, 1996).…”
Section: Introductionsupporting
confidence: 73%
“…After 18 days of incubation, the 13 C-labelled bacterial community consisted mainly of members of the Nitrospira phylum, and to a minor extent of members of the Firmicutes and the candidate division 'Endomicrobia'. The Nitrospira phylum contains among others the iron reducer candidatus 'Magnetobacterium bavaricum' (Spring et al, 1993) and the sulfur reducers Thermodesulfovibrio yellowstonii and T. islandicus (Henry et al, 1994;Sonne-Hansen and Ahring, 1999), which, however, showed only about 87-88% sequence similarity to sequences retrieved in this study (Fig. 5).…”
Section: Figmentioning
confidence: 57%
“…Thus MTB do not form a coherent phylogenetic group. While most of the freshwater MTB like the magnetospirilla and the marine strains MC-1 and MV-1 belong to the Alphaproteobacteria (Williams et al, 2006), magnetotactic representatives are also scattered within the Deltaproteobacteria and the Nitrospira phyla (DeLong et al, 1993;Spring et al, 1993;Sakaguchi et al, 2002), and there are some indications for the presence of greigite-producing MTB within the Gammaproteobacteria (Simmons et al, 2004). Because of this phylogenetic diversity, the origin of magnetotaxis was initially thought to be the result of independent evolutionary processes in distinct phyla (DeLong et al, 1993); however, recent findings suggest this diversity and the wide distribution of the magnetotactic phenotype is a result of horizontal gene transfer (HGT) (Schübbe et al, 2003;Ullrich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%